PENGARUH KENAIKAN INVESTASI SWASTA DAN PENGELUARAN PEMERINTAH DAERAH TERHADAP KETIMPANGAN PEMBANGUNAN DI KALIMANTAN BARAT - Heny Sucihati, B61109044 (Jurnal Ekonomi Daerah (JEDA), 2016)
ABSTRACKThe effect of rising private investment and government expenditure AgainstInequality Regional Development In Kalimantan BaratThis study aims to examine the implementation of the Kuznets curve